Sujud Sumarah sebagai Mediasi Coping dalam Menghadapi Berbagai Masalah Hidup - Shelli Septiayu Risandy; Hamid Nasuki (Inklusiva: Jurnal Studi Agama-Agama, 2026)
Sumarah, an indigenous Javanese spirituality (Kejawen), centers on the philosophy of total surrender to God Almighty through a meditation practice known as Sujud Sumarah. This study aims to explore the practice of Sujud Sumarah as a coping strategy for dealing with various life stressors. It examines the internalization of local spiritual values ​​in building personal resilience. A descriptive qualitative approach was employed, utilizing methods such as in-depth interviews with members of the Sumarah group and direct observation. The findings reveal that Sujud Sumarah is not merely a passive activity but an active practice involving three key stages: emotional acceptance (nrimo), letting go of the ego (pasrah), and aligning oneself with God's will (sumarah). The practice proved effective in reducing anxiety levels, fostering inner peace (tentrem), and altering individuals' perceptions of stressors. Thus, it can be concluded that spirituality-based local wisdom holds significant potential as a form of psychological intervention.